Biodegradable polyester resin, method for producing the same, and biodegradable polyester molded article containing the same
Patent Information
- Application Number
- JP2024040545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-25
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-05-25
AI Technical Summary
【0013】 本発明の一実施例による生分解性ポリエステル樹脂は、第1ジオール残基および芳香族ジカルボン酸の残基を含む第1繰り返し単位と、第2ジオール残基および脂肪族ジカルボン酸の残基を含む第2繰り返し単位とが、特定範囲の繰り返し単位の数の比を有し、樹脂の衝撃強度指数が特定範囲以上を満足することにより、前記生分解性ポリエステル樹脂は、従来に使用されていた生分解性樹脂に比べ、衝撃吸収エネルギーおよび硬度をより向上させ得る。
Smart Images

Figure 0007936832000023 
Figure 0007936832000001 
Figure 0007936832000002
Abstract
Description
[Technical Field]
[0001] This invention relates to a biodegradable polyester resin, a method for producing the same, and a biodegradable polyester molded article containing the same. [Background technology]
[0002] In recent years, as concerns about environmental issues have grown, solutions to the disposal problems of various everyday products, especially disposable products, are being sought. Specifically, polymer materials are inexpensive and have excellent properties such as processability, and are widely used to manufacture a variety of products such as films, fibers, packaging materials, bottles, and containers. However, when used products reach the end of their lifespan, they release harmful substances when incinerated, and some types take hundreds of years to decompose completely naturally.
[0003] To overcome the limitations of such polymers, research on biodegradable polymers that decompose quickly is being actively conducted. Examples of biodegradable polymers used include polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), and polybutylene succinate (PBS). While these biodegradable polymers offer excellent flexibility and easy stretching, they often suffer from poor impact resistance, leading to problems such as tearing or bursting when used in finished products. Furthermore, their inferior hardness properties make it difficult to expand their applications to diverse uses such as injection molding, thus limiting their overall use.
[0004] To overcome these limitations, methods have been employed that involve adding additives such as impact strength improvers or compatibilizers. However, this has the drawback of negatively affecting biodegradability and causing microplastic problems.
[0005] Therefore, there is a need to develop polymer resins that are biodegradable while also having improved impact resistance and durability, enabling a wide range of applications.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0007] An object of the present invention is to provide a polyester resin having excellent physical properties such as impact absorption energy and hardness, as well as excellent impact resistance and durability, and a method for producing the same.
[0008] Furthermore, another object of the present invention is to provide an eco-friendly biodegradable polyester molded article that achieves the aforementioned excellent physical properties using the polyester resin, and also has excellent biodegradability and water degradability.
Means for Solving the Problems
[0009] The present invention provides a biodegradable polyester resin comprising a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, wherein the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) represented by the following formula 1 is 2.2 or more.
[0010] [Formula 1] JPEG0007936832000001.jpg13128 In the aforementioned Formula 1, IA and H3T are values excluding units, measured on a biodegradable polyester sheet test piece produced from the biodegradable polyester resin, IA is the impact absorption energy (kJ / m) when a 10cm x 10cm test specimen is struck with a triangular pyramidal head with a diameter of 16mm and a height of 14mm. H3T is the hardness of a 3mm thick specimen measured using a Shore D hardness tester, based on ISO 868 and ASTM D2240.
[0011] Furthermore, the present invention provides a method for producing a biodegradable polyester resin comprising: a first step of mixing a diol component and an aromatic dicarboxylic acid and pre-treating it to obtain a slurry; a second step of performing an esterification reaction at least once using a mixture containing the slurry and an aliphatic dicarboxylic acid, or a mixture containing a reaction product obtained by esterifying the slurry and an aliphatic dicarboxylic acid, to obtain a prepolymer; and a third step of performing a condensation polymerization reaction on the prepolymer, wherein the biodegradable polyester resin comprises a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, wherein the ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by formula 1 is 2.2 or higher.
[0012] Furthermore, the present invention provides a biodegradable polyester molded article comprising a biodegradable polyester resin, wherein the biodegradable polyester resin comprises a first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit comprising a second diol residue and an aliphatic dicarboxylic acid residue, the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by formula 1 is 2.2 or higher. [Effects of the Invention]
[0013] In one embodiment of the present invention, a biodegradable polyester resin has a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, with a ratio of the number of repeating units within a specific range. By satisfying that the impact strength index of the resin is above a specific range, the biodegradable polyester resin can further improve impact absorption energy and hardness compared to conventionally used biodegradable resins.
[0014] Furthermore, since the biodegradable polyester resin can provide biodegradable polyester sheets, films, and molded products that are biodegradable yet have excellent impact resistance, durability, and moldability, it can be used in a variety of fields requiring durability, such as injection molded products, 3D filaments, and interior building materials, and can exhibit excellent properties. [Brief explanation of the drawing]
[0015] [Figure 1] Figure 1 schematically shows a method for preparing biodegradable polyester resin based on an example of its implementation. [Modes for carrying out the invention]
[0016] The present invention will be described in more detail below. In this specification, when a part is said to "include" a component, unless otherwise stated, this means that it may include other components rather than excluding them.
[0017] Furthermore, all numerical ranges indicating physical properties, dimensions, etc., of the components described herein should be understood to be modified by the term "approximately" in all cases, unless otherwise specified.
[0018] In this specification, terms such as first, second, primary, and secondary are used to describe various components, and such components are not limited to those terms. The terms are used solely for the purpose of distinguishing one component from another.
[0019] In one embodiment of the present invention, a biodegradable polyester resin is provided, comprising a first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit comprising a second diol residue and an aliphatic dicarboxylic acid residue, wherein the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by the following formula 1 is 2.2 or higher.
[0020] [Formula 1] In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a 10cm x 10cm test specimen is struck with a triangular pyramidal head with a diameter of 16mm and a height of 14mm. H3T is the hardness measured on a 3mm thick specimen using a Shore D hardness tester, based on ISO 868 and ASTM D2240.
[0021] Generally, biodegradable polyester resins, such as polybutylene adipate terephthalate (PBAT) resins, have excellent flexibility but poor impact resistance, making them prone to tearing and bursting, and their low stiffness has severely limited their applications. However, in order to enable diverse applications such as molded products like injection-molded items, it is extremely important to improve impact resistance and durability while still allowing for proper biodegradation.
[0022] To achieve this, it is necessary to realize not only physical properties such as strength, but also physical properties such as impact absorption energy, hardness, and thermal shrinkage rate at appropriate levels. Furthermore, in order to utilize the biodegradable polyester resin in a variety of applications such as biodegradable polyester films and molded products such as injection-molded products, it is necessary that bubble formation is performed well during the inflation film process, that there is no fusion between film surfaces during winding, and that during injection molding at high temperatures of 190°C or higher, the film does not fuse to the mold surface and deformation such as shrinkage is minimized.
[0023] Therefore, in order to achieve the aforementioned properties of biodegradable polyester resin, it is extremely important to control the structure, impact strength, impact absorption energy, hardness, and thermal deformability of the biodegradable polyester resin.
[0024] In one embodiment of the present invention, the biodegradable polyester resin comprises a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue. By adjusting the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) to a specific range, and simultaneously controlling the impact strength index of the resin to a specific range, the impact absorption energy and hardness can be further improved. This provides a biodegradable polyester sheet or film that has a low thermal shrinkage rate, as well as excellent impact resistance, durability, and moldability, while ultimately being biodegradable.
[0025] Furthermore, the biodegradable polyester resin has technical significance in that its applications can be extended not only to sheets or films having the aforementioned properties, but also to molded products, such as injection-molded products (disposable), 3D filaments, and interior building materials. The following provides a more detailed explanation of biodegradable polyester resins.
[0026] [Biodegradable polyester resin] A biodegradable polyester resin according to one embodiment of the present invention comprises a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue.
[0027] The first diol residue and the second diol residue each include a residue of 1,4-butanediol, 1,2-ethanediol, 1,3-propanediol, or a derivative thereof; the aromatic dicarboxylic acid residue includes a residue of terephthalic acid, dimethyl terephthalate, or a derivative thereof; and the aliphatic dicarboxylic acid residue includes a residue of adipic acid, succinic acid, sebacic acid, or a derivative thereof.
[0028] The biodegradable polyester resin having the above structure can improve the biodegradability, water degradability, and mechanical properties of biodegradable polyester sheets, films, or molded articles produced thereby.
[0029] The diol residue includes residues of 1,4-butanediol, 1,2-ethanediol, 1,3-propanediol, or derivatives thereof, more specifically including residues of 1,4-butanediol, 1,2-ethanediol, or derivatives thereof, and more specifically, may include residues of 1,4-butanediol or derivatives thereof. For example, if the diol includes 1,4-butanediol, it may be even more advantageous in improving the biodegradability, water degradability, and mechanical properties of biodegradable polyester resin, or biodegradable polyester sheets, films, or molded articles obtained using the same.
[0030] Furthermore, if the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid each contain the aforementioned components, the preparation process of the present invention can react more uniformly with the diol component, thereby increasing reaction efficiency, which may be even more advantageous for preparing a biodegradable polyester resin having the aforementioned physical properties.
[0031] Specifically, the first diol residue and the second diol residue each include a residue of 1,4-butanediol or a derivative thereof, the aromatic dicarboxylic acid residue includes a residue of terephthalic acid or a derivative thereof, and the aliphatic dicarboxylic acid residue may include a residue of adipic acid, succinic acid, or a derivative thereof.
[0032] For example, the biodegradable polyester resin may contain a first repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of terephthalic acid or a derivative thereof.
[0033] Alternatively, the biodegradable polyester resin may include a first repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of dimethyl terephthalate or a derivative thereof.
[0034] The biodegradable polyester resin may contain a second repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of adipic acid or a derivative thereof.
[0035] Alternatively, the biodegradable polyester resin may contain a second repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of succinic acid or a derivative thereof.
[0036] A biodegradable polyester resin according to an embodiment of the present invention may comprise a first repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of terephthalic acid or a derivative thereof; and a second repeating unit comprising a residue of 1,4-butanediol or a derivative thereof and a residue of adipic acid or a derivative thereof.
[0037] When the first repeating unit and the second repeating unit satisfy the above configuration, it may be more advantageous to provide a biodegradable polyester sheet, film, or molded article with improved physical properties while maintaining excellent biodegradability and water degradability.
[0038] On the other hand, in order to provide a sheet, film, or molded product in which the biodegradable polyester resin is biodegradable yet offers excellent impact resistance and durability, as well as excellent inflation moldability and injection moldability at high temperatures, and minimizes shape deformation such as thermal shrinkage, it is extremely important to adjust the number of repeating units that make up the biodegradable polyester resin.
[0039] According to an embodiment of the present invention, the ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) can be 0.8 to 3.0. Specifically, the ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) can be 0.82 to 3.0, 0.83 to 3.0, 0.9 to 2.8, 0.9 to 2.5, 0.9 to 2.4, 1.0 to 2.4, 1.1 to 2.4, 1.3 to 2.4, or 1.4 to 2.4.
[0040] If the ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is less than the range, the impact absorption energy and hardness may decrease, and the thermal shrinkage rate may increase excessively. In particular, during the inflation film process using the biodegradable polyester resin, the bubble shape may not be properly aligned, or it may stretch unevenly to one side, or the bubbles may burst, resulting in poor inflation moldability. Alternatively, during injection molding, the biodegradable polyester resin, sheet, or film may fuse to the mold surface of the injection machine, making it difficult to remove, or shape deformation such as shrinkage may occur.
[0041] Specifically, the number of the first repeating units may be 150-900, 180-900, 200-900, 300-900, 360-900, 380-800, 400-800, 410-780, 420-750, or 420-740.
[0042] The number of the second repeating units may be 150-600, 180-550, 200-500, 220-490, 230-490, 250-460, 280-440, or 300-430.
[0043] When the number of the first repeating units and the number of the second repeating units each satisfy the aforementioned range, the physical properties of the biodegradable polyester resin or biodegradable polyester sheets, films, or molded articles manufactured therefrom, such as impact resistance and durability, can be improved, the thermal shrinkage rate can be reduced, processability can be improved during the inflation film process or injection molding, and fusion or shape deformation can be minimized.
[0044] In particular, by controlling the number of the second repeating units within the range described above, the biodegradable polyester resin, or the biodegradable polyester sheet, film, or molded article obtained using it, becomes even tougher, and the desired impact absorption energy and hardness can be achieved through a combined improvement in strength and elongation.
[0045] In one embodiment of the present invention, the number of first repeating units may be the same as the number of second repeating units, or the number of first repeating units may be greater. In this case, it may be even more advantageous to achieve the effects intended in the present invention.
[0046] Specifically, the more the number of the second repeating units containing the second diol residue and aliphatic dicarboxylic acid residue, the higher the elongation of the sheet using the biodegradable polyester resin may be, but the impact absorption energy and hardness may decrease. As a result, the impact resistance and durability of the biodegradable polyester film or molded product produced may deteriorate, and problems such as shrinkage or deformation at high temperatures may occur.
[0047] On the other hand, if the number of the first repeating units is the same as the number of the second repeating units, or if the number of the first repeating units is greater, the above problem can be solved, and the effects intended in the present invention can be effectively achieved. In particular, the biodegradable polyester resin according to the embodiment of the present invention has excellent durability even if decomposition occurs slowly, so it can be usefully used in building interior materials and injection molded products, and it can ultimately undergo biodegradation while guaranteeing excellent durability over a specific period.
[0048] A biodegradable polyester resin according to one embodiment of the present invention has an impact strength index (ISI) of 2.2 or higher, as shown in Formula 1 below.
[0049] [Formula 1] JPEG0007936832000003.jpg13128 In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a 10cm x 10cm test specimen is struck with a triangular pyramidal head with a diameter of 16mm and a height of 14mm. H3T is the hardness measured on a 3mm thick specimen using a Shore D hardness tester, based on ISO 868 and ASTM D2240.
[0050] The impact strength index (ISI) expressed by formula 1 is an index indicating the degree of impact resistance and durability of biodegradable polyester sheets, films, or molded articles manufactured from biodegradable polyester resin, and is the value obtained by dividing the product of the impact absorption energy (IA) and hardness (H3T) of the biodegradable polyester resin by 100.
[0051] The impact strength index (ISI) is higher when it is high, which may indicate greater impact resistance and / or durability. Furthermore, the impact strength index (ISI) is higher when the impact absorption energy (IA) and / or hardness (H3T) of the biodegradable polyester resin is high.
[0052] When an impact strength index (ISI) with such characteristics satisfies the appropriate range, it can simultaneously improve the impact resistance and durability of biodegradable polyester sheets, films, and molded articles manufactured from biodegradable polyester resin.
[0053] Specifically, the impact strength index (ISI) of the biodegradable polyester resin is, for example, 2.2 or higher, for example, 2.3 or higher, or for example, 3.0 or higher, and may be, for example, 2.2 to 5.0, for example, 2.3 to 5.0, for example, 2.5 to 5.0, for example, 2.2 to 4.0, for example, 2.3 to 4.0, for example, 3.0 to 4.0, for example, 3.0 to 5.0, for example, 3.0 to 4.0, or for example, 3.0 to 3.5. When the impact strength index (ISI) of the biodegradable polyester resin satisfies 2.2 or higher, specifically 2.2 to 5.0, the impact resistance and durability of the biodegradable polyester sheet, film, or molded product are appropriate, and it can be utilized in various fields and exhibit excellent properties.
[0054] If the impact strength index (ISI) of the biodegradable polyester resin is less than 2.2, the impact absorption energy (IA) and / or hardness (H3T) of the biodegradable polyester resin will be too low, which may adversely affect the impact resistance and durability of biodegradable polyester sheets, films, or molded products manufactured from the biodegradable polyester resin. It may also adversely affect moldability, such as inflation moldability and injection moldability. In particular, due to poor adhesive properties, the surfaces of the film may stick together during winding, resulting in poor inflation moldability.
[0055] In Equation 1, the impact absorption energy (KJ / m) of the biodegradable polyester resin represented by IA is calculated by dividing the amount of impact absorption energy by the thickness when a biodegradable polyester sheet test piece with an area of 10 cm × 10 cm is struck with a triangular pyramidal head with a diameter of 16 mm and a height of 14 mm in a Film Impact Test, and is shown in Equation 7 below.
[0056] [Formula 7] Impact absorption energy (IA) (kJ / m) = Amount of impact absorption energy (kJ) / Thickness (m)
[0057] In this case, the biodegradable polyester sheet is in its unstretched state, which may be similar to or identical to the physical properties of the biodegradable polyester resin.
[0058] The aforementioned impact absorption energy indicates the toughness of a surface containing a velocity factor; a higher amount of impact absorption energy may indicate higher impact strength.
[0059] The impact absorption energy (KJ / m) of the biodegradable polyester resin is 6.0 KJ / m or more, for example 6.2 KJ / m or more, or for example 7.2 KJ / m or more, and can be, for example, 6.0 KJ / m to 10.0 KJ / m, for example 6.0 KJ / m to 9.5 KJ / m, for example 6.0 KJ / m to 9.0 KJ / m, for example 6.2 KJ / m to 9.5 KJ / m, for example 6.2 KJ / m to 8.5 KJ / m, for example 7.1 KJ / m to 9.0 KJ / m, or for example 7.1 KJ / m to 8.5 KJ / m.
[0060] If the impact absorption energy (kJ / m) of the biodegradable polyester resin satisfies the above range, the impact strength is appropriate, which may be advantageous in terms of impact resistance and durability of the biodegradable polyester sheet, film, or molded product manufactured from the biodegradable polyester resin.
[0061] In Formula 1, the hardness (Shore D) of the biodegradable polyester resin exhibiting H3T is a measure of the hardness of the material, and a higher hardness indicates greater hardness of the sheet, film, or molded surface.
[0062] The hardness (Shore D) can be measured using a DeFelsko Shore D tester after preparing a 3 mm thick biodegradable polyester sheet test specimen using biodegradable polyester resin, in accordance with ISO 868 and ASTM D2240. In this case, the biodegradable polyester sheet is in its unstretched state, and its physical properties may be similar to or identical to those of the biodegradable polyester resin.
[0063] The hardness (Shore D) of the biodegradable polyester resin is 32 or higher, for example 38 or higher, or for example 42 or higher, and may be, for example 32-50, for example 38-50, for example 42-50, or for example 42-48.
[0064] When the hardness (Shore D) of the biodegradable polyester resin satisfies the aforementioned range, it is even more advantageous in achieving the impact strength index targeted in the present invention, and is advantageous in terms of impact resistance and durability, thus enabling diverse applications in various molded products.
[0065] On the other hand, the biodegradable polyester resin has a thermal shrinkage rate (TS) expressed by the following formula 2. 50 ) may be 30% or less.
[0066] [Formula 2] In the above formula 2, L 25 This is the initial length of a biodegradable polyester film test specimen manufactured from biodegradable polyester resin at 25°C. L 50 This is the length of a biodegradable polyester film test specimen made from biodegradable polyester resin after being exposed to a 50°C hot air blower for 5 minutes.
[0067] The thermal shrinkage coefficient (TS) expressed in the above formula 2 50 This value represents the degree of thermal shrinkage of a biodegradable polyester film test specimen at a hot air temperature of 50°C, converted to a percentage. It is the percentage change between the initial length of the biodegradable polyester film test specimen and the length of the test specimen after being exposed to hot air.
[0068] The aforementioned thermal shrinkage rate (TS 50 The length can be calculated by cutting a biodegradable polyester film into 150 mm long and 2 cm wide pieces, regardless of direction, to make test specimens, and then measuring the initial length at room temperature and the length of the biodegradable polyester film test specimens after being left in a 50°C convection (hot air) oven for 5 minutes.
[0069] The thermal shrinkage rate (TS 50 ) may be less than 30%, 28% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 20% or less, less than 20%, 18% or less, or 15% or less.
[0070] The thermal shrinkage rate (TS 50 ) satisfies the value not greater than the aforementioned range, the degree of thermal shrinkage is low at a high hot air temperature of 50°C or higher, the inflation moldability or injection moldability can be further improved, and at the same time, the physical properties of the biodegradable polyester film or molded article can be improved, which can be further advantageous for expanding various application fields.
[0071] Meanwhile, according to an embodiment of the present invention, the biodegradable polyester resin may have a thermal deformation index (TD 50 ) represented by the following Formula 3 of 0.15 or less.
[0072] [Formula 3] JPEG0007936832000005.jpg12128 In the Formula 3, TS 50 and ISI are as defined above.
[0073] The thermal deformation index (TD 50 ) represented by the Formula 3 is an index indicating the degree of thermal deformation of a biodegradable polyester sheet, film, or molded article at a hot air temperature of 50°C with respect to impact strength, and may vary depending on the thermal shrinkage rate (TS 50 ) and the impact strength index (ISI). That is, the thermal deformation index (TD 50 ) is a value obtained by dividing the value obtained by dividing the thermal shrinkage rate of a biodegradable polyester film test piece produced using the biodegradable polyester resin by 100, by the impact strength index (ISI) of the biodegradable polyester resin (sheet test piece).
[0074] The thermal deformation index (TD 50) could be, for example, 0.14 or less, for example, 0.12 or less, for example, 0.11 or less, for example, 0.10 or less, for example, 0.08 or less, for example, less than 0.08, or for example, 0.07 or less.
[0075] The aforementioned thermal deformation index (TD 50 If the above range is satisfied, the degree of thermal deformation with respect to impact strength at high hot air temperatures of 50°C or higher is small, which can improve durability and heat resistance, further improve inflation moldability or injection moldability, and at the same time improve the physical properties of biodegradable polyester sheets, films or molded articles, which may be even more advantageous for expanding to a wide range of applications.
[0076] On the other hand, the biodegradable polyester resin may have a loss tangent (tanδ) greater than 1, as shown in the following formula 4.
[0077] JPEG0007936832000006.jpg2061 In the above formula 4, G' is the storage modulus of the biodegradable polyester sheet produced from the biodegradable polyester resin at 240°C and a frequency of 5 rad / s in dynamic viscoelasticity measurements. G'' is the loss modulus of the biodegradable polyester sheet produced from the biodegradable polyester resin at 240°C and a frequency of 5 rad / s in dynamic viscoelasticity measurements.
[0078] The storage modulus and loss modulus of the polyester sheet may refer to the storage modulus and loss modulus of the polyester resin.
[0079] The loss tangent (tanδ) of the biodegradable polyester resin can be calculated using Equation 4 after forming the biodegradable polyester resin into a sheet using a dynamic viscoelasticity testing machine, RDS (Rheometrics Dynamic Spectrometer, TA Instrument, Discovery HR 30), and then measuring the storage modulus and loss modulus.
[0080] In other words, the loss tangent (tanδ) of the biodegradable polyester resin is the ratio of the loss modulus (G'') of the biodegradable polyester resin to the storage modulus (G') of the biodegradable polyester resin, and if the value of the loss modulus (G'') of the biodegradable polyester resin is greater than the value of the storage modulus (G') of the biodegradable polyester resin, that is, the loss tangent (tanδ) of the biodegradable polyester resin expressed in formula 4 may exceed 1.
[0081] Specifically, the loss tangent (tanδ) of the biodegradable polyester resin may be, for example, 1.05 to 1.30, 1.05 to 1.25, 1.10 to 1.25, 1.10 to 1.20, or 1.15 to 1.19.
[0082] When the loss tangent (tanδ) of the biodegradable polyester resin satisfies the above range, the impact resistance, durability, and moldability of the biodegradable polyester sheet, film, or molded product manufactured from the biodegradable polyester resin can be simultaneously improved, the impact absorption energy and strength can be enhanced, and the thermal shrinkage rate and thermal deformation can be minimized.
[0083] The storage modulus (G') of the biodegradable polyester resin can be measured after forming a sheet using the biodegradable polyester resin, in which case it can be, for example, 200,000 dyne / cm². 2 ~400,000 dyne / cm 2 For example, 250,000 dyne / cm² 2 ~400,000 dyne / cm 2 For example, 280,000 dyne / cm² 2~400,000 dyne / cm 2 For example, 300,000 dyne / cm² 2 ~380,000 dyne / cm 2 , or for example, 310,000 dyne / cm² 2 ~360,000 dyne / cm 2 It is possible.
[0084] The loss modulus (G'') of the biodegradable polyester resin can be measured after forming a sheet using the biodegradable polyester resin, in which case it can be, for example, 220,000 dyne / cm². 2 ~450,000 dyne / cm 2 For example, 270,000 dyne / cm² 2 ~430,000 dyne / cm 2 For example, 290,000 dyne / cm² 2 ~430,000 dyne / cm 2 For example, 310,000 dyne / cm² 2 ~420,000 dyne / cm 2 , or for example, 330,000 dyne / cm² 2 ~400,000 dyne / cm 2 It is possible.
[0085] When the storage modulus (G') and loss tangent (tanδ) of the biodegradable polyester resin satisfy the aforementioned ranges, the impact resistance, durability, and moldability of biodegradable polyester sheets, films, or molded articles manufactured from the biodegradable polyester resin can be simultaneously improved, impact absorption energy and strength can be enhanced, and thermal shrinkage and thermal deformation can be minimized.
[0086] On the other hand, the biodegradable polyester film containing the biodegradable polyester resin may have a biodegradation rate of 50% or more, as measured by the amount of carbon dioxide generated based on KS M3100-1, and a water decomposition rate reduction rate of 50% or more, as shown in the following formula 5.
[0087] [Formula 5] In the above formula 5, Mn A and Mn B This refers to the number-average molecular weight of the biodegradable polyester sheet, which was manufactured from the biodegradable polyester resin, after being immersed in water and accelerated in a convention (hot air) oven at 80°C, and then measured using gel permeation chromatography (GPC). Mn A This is the initial number-average molecular weight of the biodegradable polyester sheet, Mn B This is the number-average molecular weight of the biodegradable polyester sheet three months after the acceleration of water splitting was implemented.
[0088] The aforementioned accelerated water splitting means immersing the biodegradable polyester sheet in water and hydrolyzing it at a temperature of 80°C.
[0089] The rate of decrease in the degree of water decomposition can be calculated by measuring the initial number-average molecular weight of the biodegradable polyester sheet and the number-average molecular weight three months after the acceleration of water decomposition is implemented. That is, the rate of decrease in the degree of water decomposition of the biodegradable polyester sheet is expressed as a percentage of the difference between the initial number-average molecular weight and the number-average molecular weight of the biodegradable polyester sheet three months later, using gel permeation chromatography (GPC) with respect to the initial number-average molecular weight expressed by formula 5.
[0090] The rate of decrease in the degree of water decomposition of the biodegradable polyester sheet may be 50% or more, 52% or more, 54% or more, 55% or more, 58% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more.
[0091] By ensuring that the rate of decrease in the degree of water decomposition of the biodegradable polyester sheet satisfies the aforementioned range, it becomes possible to achieve biodegradation while also ensuring durability. In other words, a biodegradable polyester sheet, film, or molded article according to one embodiment of the present invention has the advantage that decomposition proceeds slowly, but long-term durability can be maintained.
[0092] The initial number-average molecular weight (Mn) of the biodegradable polyester sheet. A ) can range from 50,000 g / mol to 70,000 g / mol, for example, 50,000 g / mol to 68,000 g / mol or 50,000 g / mol to 65,000 g / mol.
[0093] After immersing the biodegradable polyester sheet in water at 80°C, the number-average molecular weight (Mn) of the biodegradable polyester sheet was measured after 3 months of accelerated water decomposition. B ) may range from 3000 g / mol to 40000 g / mol, for example, 4000 g / mol to 35000 g / mol or 5000 g / mol to 30000 g / mol.
[0094] The initial number-average molecular weight (Mn) of the biodegradable polyester sheet A ) and the number-average molecular weight (Mn) of the biodegradable polyester sheet three months after the implementation of accelerated water splitting. B If each of the ranges of ) satisfies the aforementioned range, the rate of decrease in the degree of water decomposition can be satisfied within the aforementioned range, and thus biodegradation may be possible under seawater decomposition or humidification conditions.
[0095] The structure and physical properties of the biodegradable polyester resin according to one embodiment of the present invention can be efficiently achieved by utilizing the method for producing the biodegradable polyester resin according to one embodiment of the present invention.
[0096] The method for producing the biodegradable polyester resin will be described in detail below.
[0097] [Method for producing biodegradable polyester resin] In another embodiment of the present invention, a method for producing a biodegradable polyester resin is provided, comprising: a first step of mixing a diol component and an aromatic dicarboxylic acid and pre-treating it to obtain a slurry; a second step of performing an esterification reaction at least once using a mixture containing the slurry and an aliphatic dicarboxylic acid, or a mixture containing a reaction product obtained by esterifying the slurry and an aliphatic dicarboxylic acid, to obtain a prepolymer; and a third step of performing a condensation polymerization reaction on the prepolymer, wherein the biodegradable polyester resin comprises a first repeating unit containing a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, wherein the ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by formula 1 is 2.2 or higher.
[0098] According to an embodiment of the present invention, the method for producing the biodegradable polyester resin involves mixing a diol component with an aromatic dicarboxylic acid and pretreating the mixture to obtain a slurry, then using that slurry to carry out an esterification reaction to obtain a prepolymer, and finally carrying out a condensation polymerization reaction on the prepolymer. This method efficiently achieves the desired structure and physical properties of the biodegradable polyester resin as described in the embodiment of the present invention.
[0099] Referring to Figure 1, the method for producing the biodegradable polyester resin (S100) includes a first step (S110) of mixing a diol component with an aromatic dicarboxylic acid and pre-treating it to obtain a slurry.
[0100] In other words, the first step is a pretreatment step before the esterification reaction, in which the diol component and the aromatic dicarboxylic acid are mixed and formed into a slurry.
[0101] By mixing the diol component with the aromatic dicarboxylic acid and pre-treating it to form a slurry, not only can the diol component and the aromatic dicarboxylic acid react uniformly, but it is also effective in accelerating the esterification reaction, thus increasing the reaction efficiency.
[0102] In particular, when aromatic dicarboxylic acids, such as terephthalic acid, are perfectly crystalline and in powder form, their solubility in the diol is very low, which can make homogeneous reactions difficult. Therefore, the slurrying pretreatment process can play a very important role in providing biodegradable polyester resins, sheets, films, and molded articles with excellent physical properties as demonstrated in the embodiment of the present invention, and in increasing reaction efficiency.
[0103] Furthermore, if the diol component and aromatic dicarboxylic acid are mixed together without a pretreatment step, and the esterification reaction is carried out by mixing all of them together, the reaction between the diol component and the aliphatic dicarboxylic acid may occur first. This can make it difficult to achieve a biodegradable polyester resin that satisfies the ratio (X / Y) of the number of first repeating units and second repeating units targeted in the present invention.
[0104] In an embodiment of the present invention, when the aromatic dicarboxylic acid is terephthalic acid, the terephthalic acid has perfect crystalline properties, is a white crystal that sublimes at around 300°C at atmospheric pressure without a melting point, and has very low solubility in the diol, making a homogeneous reaction difficult. Therefore, performing a pretreatment step before the esterification reaction increases the surface area for reaction with the diol within the solid matrix of terephthalic acid, thereby inducing a homogeneous reaction.
[0105] Furthermore, in the embodiment of the present invention, when the aromatic dicarboxylic acid is dimethyl terephthalate, the pretreatment process allows the dimethyl terephthalate to be melted at approximately 142°C to 170°C and reacted with the diol, thereby enabling a faster and more efficient esterification reaction.
[0106] On the other hand, in the first pretreatment step, the structure and physical properties of the biodegradable polyester resin may change depending on the particle size, particle size distribution, and pretreatment reaction conditions of the aromatic dicarboxylic acid.
[0107] For example, the aromatic dicarboxylic acid includes terephthalic acid, and the terephthalic acid has an average particle size (D50) of 10 μm to 400 μm as measured by a Microtrac® S3500 particle size analyzer (Microtrac Inc.) in its particle size distribution (PSD), and the standard deviation of the average particle size (D50) may be 100 or less. The standard deviation refers to the square root of the variance.
[0108] The average particle size (D50) of the terephthalic acid can be, for example, 20 μm to 200 μm, for example, 30 μm to 180 μm, or for example, 50 μm to 100 μm. When the average particle size (D50) of the terephthalic acid satisfies the above range, it may be more advantageous in terms of improved solubility in diols and reaction rate.
[0109] If the average particle size (D50) of terephthalic acid is less than 10 μm, it is undesirable because the average particle size is too small and can change from single primary particles to aggregated secondary particles. If the average particle size (D50) of terephthalic acid exceeds 400 μm, the average particle size is too large, which reduces its solubility in the diol, slows the reaction rate, and may make it difficult to obtain a homogenization reaction.
[0110] Furthermore, the standard deviation of the average particle size (D50) of terephthalic acid may be 100 or less, for example, 5 to 90, for example, 5 to 80, or for example, 5 to 70. When the standard deviation of the average particle size (D50) of terephthalic acid satisfies the above range, it may be more advantageous in terms of improved solubility in diols and reaction rate.
[0111] Furthermore, if the average particle size (D50) and standard deviation of the terephthalic acid satisfy the above range, the reaction time can be shortened by 1.5 times or more, which is preferable from the viewpoint of reaction efficiency.
[0112] When the aromatic dicarboxylic acid is dimethyl terephthalate, the average particle size (D50) and standard deviation may be similar to those of terephthalic acid when used in a molten state or measured in particulate state.
[0113] In the first pretreatment step, the diol and the aromatic dicarboxylic acid may be mixed and put into a slurry agitator (tank).
[0114] According to an embodiment of the present invention, in the first pretreatment step, the stirring force until slurry formation is extremely important, therefore the number and shape of the stirring blades of the stirrer and the conditions of the slurry formation step are extremely important.
[0115] For example, a slurry agitator with an anchor-type base, a height of 20 mm or more to the agitator, and equipped with two or more rotating blades may be more advantageous for achieving efficient stirring.
[0116] For example, the slurry agitator may be positioned at a height of 20 mm or more from the agitator, meaning that the reactor and the bottom of the agitator may be almost touching. In this case, a slurry can be obtained without sedimentation. If the shape of the agitator and the number of rotor blades do not satisfy the above conditions, the aromatic dicarboxylic acid may settle to the bottom when the diol and aromatic dicarboxylic acid are initially mixed, which can lead to phase separation.
[0117] The first pretreatment step may include mixing the diol component with the aromatic dicarboxylic acid and stirring at 60°C to 100°C at 50 rpm to 200 rpm for 10 minutes or more, for example, 10 to 200 minutes. If the pretreatment step satisfies the temperature, speed, and stirring time, a uniform slurry can be obtained without phase separation, which is advantageous in terms of reaction efficiency, and the physical properties of the biodegradable polyester resin targeted in the present invention can be efficiently obtained.
[0118] The diol component may include 1,4-butanediol, 1,2-ethanediol, 1,3-propanediol, or derivatives thereof.
[0119] Specifically, the diol component may contain 1,4-butanediol, 1,2-ethanediol, 1,3-propanediol, or derivatives thereof in amounts of 95 mol% or more, 98 mol% or more, 99 mol% or more, or 100 mol% based on the total number of moles of the diol component. By including 1,4-butanediol, 1,2-ethanediol, 1,3-propanediol, or derivatives thereof within the above ranges, the biodegradability, water degradability, and physical properties of the biodegradable polyester resin or biodegradable polyester sheets, films, or molded articles obtained using it can be improved.
[0120] The diol component may be added all at once or in stages. For example, the diol component may be added separately when mixed with the aromatic dicarboxylic acid and when mixed with the aliphatic dicarboxylic acid.
[0121] The aromatic dicarboxylic acid component may include one or more selected from the group consisting of terephthalic acid, dimethyl terephthalate, and their derivatives. Specifically, the aromatic dicarboxylic acid component may be terephthalic acid or dimethyl terephthalate.
[0122] Furthermore, the aromatic dicarboxylic acid component may be used in amounts of 45 mol% to 70 mol%, 46 mol% to 70 mol%, 48 mol% to 70 mol%, 49 mol% to 70 mol%, 50 mol% to 70 mol%, 52 mol% to 70 mol%, 55 mol% to 70 mol%, 58 mol% to 70 mol%, or 60 mol% to 70 mol%, based on the total number of moles of the dicarboxylic acid component.
[0123] Controlling the molar ratio of the aromatic dicarboxylic acid within the aforementioned range is even more advantageous in obtaining the effects of the present invention, and can further improve the impact resistance and durability of molded articles such as biodegradable polyester sheets, films, or biodegradable polyester injection molded products manufactured using the same.
[0124] Referring again to Figure 1, the method for producing the biodegradable polyester resin (S100) includes a second step (S120) of obtaining a prepolymer by carrying out an esterification reaction at least once using a mixture containing the slurry and an aliphatic dicarboxylic acid, or a mixture containing a reaction product obtained by esterifying the slurry and an aliphatic dicarboxylic acid.
[0125] The reaction time for the second esterification reaction can be shortened by using the slurry obtained in the first step. For example, by using the slurry obtained in the first step, the reaction time can be shortened by 1.5 times or more. The esterification reaction in the second step described above may be carried out at least once.
[0126] According to one embodiment of the present invention, the esterification reaction can be carried out in a single step by adding an aliphatic dicarboxylic acid, or a diol and an aliphatic dicarboxylic acid, to the slurry.
[0127] The esterification reaction may be carried out at a temperature of 250°C or lower for 0.5 to 5 hours. Specifically, the esterification reaction may be carried out at 180°C to 250°C, 185°C to 240°C, or 200°C to 240°C under atmospheric or reduced pressure until the by-product water theoretically reaches 95%. For example, the esterification reaction may be carried out for 0.5 to 4.5 hours, 0.5 to 3.5 hours, or 1 to 3 hours, but is not limited to these.
[0128] The number-average molecular weight of the prepolymer can be between 500 g / mol and 10,000 g / mol. For example, the number-average molecular weight of the prepolymer can be between 500 g / mol and 8,500 g / mol, 500 g / mol and 8,000 g / mol, 500 g / mol and 7,000 g / mol, 500 g / mol and 5,000 g / mol, or 500 g / mol and 2,000 g / mol. By satisfying the above range for the number-average molecular weight of the prepolymer, the molecular weight of the polymer can be efficiently increased in the condensation polymerization reaction.
[0129] According to yet another embodiment of the present invention, the esterification reaction may be carried out two or more times, comprising the steps of first esterifying the slurry and second esterifying the reaction product obtained from the first esterification reaction by adding an aliphatic dicarboxylic acid, or a diol and an aliphatic dicarboxylic acid.
[0130] Performing the esterification reaction two or more times offers advantages over performing it once, including improved reaction stability and uniformity, the ability to adjust the ratio of the desired number of first repeating units to the number of second repeating units, and the ability to efficiently achieve the effects shown in the embodiment of the present invention.
[0131] The primary and secondary esterification reactions may each be carried out at a temperature of 250°C or lower for 0.5 to 5 hours. Specifically, the primary and secondary esterification reactions may be carried out at 180°C to 250°C, 185°C to 240°C, or 200°C to 240°C, respectively, under atmospheric pressure until the by-product water theoretically reaches 95%. For example, the primary and secondary esterification reactions may each be carried out for 0.5 to 4.5 hours, 0.5 to 3.5 hours, or 1 to 3 hours, respectively, but are not limited to these.
[0132] The number-average molecular weight of the prepolymer can range from 500 g / mol to 10,000 g / mol. For example, the number-average molecular weight of the prepolymer can range from 500 g / mol to 8,500 g / mol, 500 g / mol to 7,000 g / mol, 1,000 g / mol to 6,000 g / mol, or 2,500 g / mol to 5,500 g / mol. By satisfying the above range for the number-average molecular weight of the prepolymer, the molecular weight of the polymer can be efficiently increased in the condensation polymerization reaction, thereby further improving the strength properties.
[0133] The aforementioned number-average molecular weight can be measured using gel permeation chromatography (GPC). Specifically, the data obtained by gel permeation chromatography includes various parameters such as Mn, Mw, and Mp, and the molecular weight can be measured using the number-average molecular weight (Mn) as the reference.
[0134] The aliphatic dicarboxylic acid component may include adipic acid, succinic acid, sebacic acid, or derivatives thereof. Specifically, the aliphatic dicarboxylic acid component may include adipic acid or succinic acid.
[0135] Furthermore, the aliphatic dicarboxylic acid component may be used in amounts of 30 mol% to 55 mol%, 30 mol% to 54 mol%, 30 mol% to 52 mol%, 30 mol% to 51 mol%, 30 mol% to 50 mol%, 30 mol% to 48 mol%, 30 mol% to 45 mol%, 30 mol% to 42 mol%, or 30 mol% to 40 mol%, based on the total number of moles of the dicarboxylic acid component.
[0136] Controlling the content of the aliphatic dicarboxylic acid within the aforementioned range is even more advantageous in obtaining the effects of the present invention, and can further improve the impact resistance and durability of molded articles such as biodegradable polyester sheets, films, or biodegradable polyester injection molded products manufactured using the same.
[0137] In particular, the aliphatic dicarboxylic acid component, being composed of linear chains, may affect the physical properties of the biodegradable polyester resin, such as impact absorption energy and hardness, as well as its inflation moldability or injection moldability.
[0138] Specifically, if the content of the aliphatic dicarboxylic acid component is too high, the impact absorption energy and hardness of the biodegradable polyester resin will decrease, and the inflation moldability and injection moldability of the biodegradable polyester sheet or film produced from the biodegradable polyester resin may deteriorate.
[0139] In the second step, nanocellulose may be further added at the esterification reaction stage, for example, at the primary esterification reaction stage, the secondary esterification reaction stage, or both, when primary and secondary esterification reactions are carried out.
[0140] Specifically, when the esterification reaction is carried out in one step, nanocellulose may be further added at the time of the esterification reaction, for example, when an aliphatic dicarboxylic acid, or when a diol and aliphatic dicarboxylic acid are added.
[0141] Furthermore, when the esterification reaction is carried out two or more times, nanocellulose can be added at the time of the primary esterification reaction, the secondary esterification reaction, or both. For example, the nanocellulose can be added at the time of the secondary esterification reaction, i.e., at the time of adding the aliphatic dicarboxylic acid, or the diol and aliphatic dicarboxylic acid, or in the early stages of the esterification reaction. This may be efficient for dispersing the nanocellulose. In particular, the addition of nanocellulose is preferable in terms of physical properties such as strength, impact absorption energy and hardness of the biodegradable polyester resin, as well as thermal properties, and can also improve the strength, impact resistance and durability of the biodegradable polyester sheet, film, or molded article.
[0142] The nanocellulose may be one or more selected from the group consisting of cellulose nanocrystals, cellulose nanofibers, microfibrillated cellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, cellulose acetate, methylcellulose, ethylcellulose, propylcellulose, butylcellulose, pentylcellulose, hexylcellulose, and cyclohexylcellulose.
[0143] The diameter of the nanocellulose may be between 1 nm and 200 nm. For example, the diameter of the nanocellulose may be between 1 nm and 150 nm, 1 nm and 120 nm, 1 nm and 100 nm, 1 nm and 95 nm, 5 nm and 90 nm, 10 nm and 80 nm, 1 nm and 50 nm, 5 nm and 45 nm, 10 nm and 60 nm, 1 nm and 10 nm, 10 nm and 30 nm, or 15 nm and 50 nm.
[0144] Furthermore, the length of the nanocellulose can range from 5 nm to 10 μm. For example, the length of the nanocellulose can range from 5 nm to 1 μm, 10 nm to 150 nm, 20 nm to 300 nm, 200 nm to 500 nm, 100 nm to 10 μm, 500 nm to 5 μm, 300 nm to 1 μm, or 1 μm to 10 μm.
[0145] By ensuring that the diameter and length of the nanocellulose satisfy the aforementioned range, the biodegradability and physical properties of the biodegradable polyester resin, or the biodegradable polyester sheets, films, and molded articles obtained using it, can be further improved.
[0146] Furthermore, the nanocellulose may be pre-treated with a bead mill or with ultrasound. Specifically, the nanocellulose may be water-dispersed nanocellulose that has been pre-treated with a bead mill or with ultrasound.
[0147] First, the bead mill pretreatment can be performed using a wet milling apparatus in a vertical or horizontal mill. A horizontal mill is preferred, but not limited to it, because it can accommodate a larger quantity of beads in the chamber, reduces uneven wear on the machine, reduces bead wear, and makes maintenance easier.
[0148] The bead mill pretreatment may be carried out using one or more beads selected from the group consisting of zirconium, zircon, zirconia, quartz, and aluminum oxide.
[0149] Specifically, the bead mill pretreatment may be carried out using beads having a diameter of 0.3 mm to 1 mm. For example, the diameter of the beads may be 0.3 mm to 0.9 mm, 0.4 mm to 0.8 mm, 0.45 mm to 0.7 mm, or 0.45 mm to 0.6 mm. By satisfying the above range for the bead diameter, the dispersibility of nanocellulose can be further improved. If the bead diameter exceeds the above range, the average particle size and particle size deviation of the nanocellulose may increase, resulting in lower dispersibility.
[0150] Furthermore, the bead mill pretreatment is preferable in that it uses beads with a specific gravity higher than that of nanocellulose, in order to transfer sufficient energy. For example, the beads are one or more selected from the group consisting of zirconium, zircon, zirconia, quartz, and aluminum oxide, which have a specific gravity higher than that of water-dispersed nanocellulose. Zirconium beads with a specific gravity four times or more higher than that of water-dispersed nanocellulose are preferred, but the material is not limited thereto.
[0151] Furthermore, the ultrasonic pretreatment is a method of physically crushing or pulverizing nanoparticles by generating waves from 20 kHz ultrasonic waves (ultrasound) released into a solution.
[0152] The ultrasonic pretreatment may be performed with an energy level of 30,000 J or less for a period of less than 30 minutes. For example, the ultrasonic pretreatment may be performed with an energy level of 25,000 J or less or 22,000 J or less for a period of 25 minutes or less, 20 minutes or less, or 18 minutes or less. By satisfying the above ranges for energy level and duration, the effect of the ultrasonic pretreatment, i.e., the improvement of dispersibility, can be maximized. If the energy level exceeds the above range, the nanoparticles may re-aggregate, resulting in lower dispersibility.
[0153] The nanocellulose in the realization example may have undergone bead mill pretreatment or ultrasonic pretreatment. Alternatively, the nanocellulose in the realization example may have undergone both bead mill pretreatment and ultrasonic pretreatment. In this case, performing ultrasonic pretreatment after bead mill pretreatment is preferable in that it prevents re-aggregation and improves dispersibility.
[0154] The polydispersity index (PDI) of the biodegradable polyester resin in the implemented examples is less than 2.0. For example, the polydispersity index of the biodegradable polyester resin may be less than 2.0, 1.95 or less, or 1.9 or less.
[0155] By adjusting the polydispersity index to the aforementioned range, the heat resistance can be further improved. Specifically, if the polydispersity index exceeds the aforementioned range, the heat resistance of the biodegradable polyester resin may decrease. Therefore, in the process of manufacturing molded products such as films using the biodegradable polyester resin, the incidence of polymer degradation may increase, resulting in lower processability and productivity. The aforementioned multivariance index can be calculated according to the following formula A.
[0156] JPEG0007936832000008.jpg2062 In the above formula A, Mw is the weight-average molecular weight (g / mol) of the resin. Mn is the number-average molecular weight (g / mol) of the resin.
[0157] Furthermore, the nanocellulose content is, for example, 3000 ppm or less, 2500 ppm or less, 2000 ppm or less, 1800 ppm or less, 1500 ppm, 1000 ppm or less, 900 ppm or less, 800 ppm or less, 700 ppm or less, 600 ppm or less, 500 ppm or less, or 400 ppm or less, based on the total weight of diols, aromatic dicarboxylic acids, and aliphatic dicarboxylic acids, and may be, for example, 100 ppm or more, 150 ppm or more, 200 ppm or more, 250 ppm or more, or 300 ppm or more. By satisfying the above range for the nanocellulose content, physical properties such as biodegradability, strength, impact absorption energy, and hardness can be further improved.
[0158] Prior to the esterification reaction in the second step, a titanium-based catalyst or a germanium-based catalyst may be further added to the slurry.
[0159] Specifically, when the esterification reaction is carried out once, a titanium-based catalyst or a germanium-based catalyst may be further added to the slurry.
[0160] Furthermore, when the esterification reaction is carried out two or more times, a titanium-based catalyst or a germanium-based catalyst may be added to the slurry, the reaction product obtained by the primary esterification reaction of the slurry, or both, before each esterification reaction.
[0161] Specifically, the biodegradable polyester resin may contain one or more titanium-based catalysts selected from the group consisting of titanium isopropoxide, antimony trioxide, dibutyltin oxide, tetrapropyl titanate, tetrabutyl titanate, tetraisopropyl titanate, antimony acetate, calcium acetate, and magnesium acetate, or one or more germanium-based catalysts selected from the group consisting of germanium oxide, germanium methoxide, germanium ethoxide, tetramethylgermanium, tetraethylgermanium, and germanium sulfide.
[0162] Furthermore, the catalyst content may range from 100 ppm to 1000 ppm based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. For example, it may include titanium-based or germanium-based catalysts in concentrations of 100 ppm to 800 ppm, 150 ppm to 700 ppm, 200 ppm to 600 ppm, or 250 ppm to 550 ppm. By satisfying the catalyst content within the above range, the physical properties can be further improved.
[0163] During the second esterification reaction, or at the end of the esterification reaction, or both, a phosphorus-based stabilizer may be added.
[0164] Specifically, when an esterification reaction is carried out once, a phosphorus-based stabilizer may be added during the esterification reaction, at the end of the esterification reaction, or both.
[0165] Furthermore, when the esterification reaction is carried out two or more times, a phosphorus-based stabilizer may be added during the primary esterification reaction, the secondary esterification reaction, or both, or at the end of the primary esterification reaction or the end of the secondary esterification reaction.
[0166] Specifically, the biodegradable polyester resin may further contain one or more phosphorus-based stabilizers selected from the group consisting of amine-based high-temperature heat stabilizers such as tetraethylenepentaamine, phosphoric acid, phosphorous acid, polyphosphate, trimethylphosphate, triethylphosphate, triethylphosphonoacetate, trimethylphosphine, and triphenylphosphine.
[0167] The content of the phosphorus-based stabilizer may be 3000 ppm or less, based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. Specifically, the content of the phosphorus-based stabilizer may be, for example, 10 ppm to 3000 ppm, 20 ppm to 2000 ppm, 20 ppm to 1500 ppm, or 20 ppm to 1000 ppm, based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. By satisfying the above range for the content of the phosphorus-based stabilizer, the degradation of the polymer due to high temperatures during the reaction process can be controlled, the end groups of the polymer can be reduced, and the color can be improved.
[0168] After the esterification reaction in the second step is completed, one or more additives selected from the group consisting of silica, potassium, or magnesium, and color correctors such as cobalt acetate may be added. That is, after the esterification reaction is completed, the additives and / or color correctors may be added to stabilize the mixture, and then the polymerization condensation reaction may be carried out.
[0169] Referring again to Figure 1, the method for producing the biodegradable polyester resin (S100) includes a third step (S130) in which the prepolymer undergoes a condensation polymerization reaction.
[0170] The aforementioned condensation polymerization reaction may be carried out at 180°C to 280°C, with a condensation rate of 1.0 torr or less, for 1 to 5 hours. For example, the aforementioned condensation polymerization reaction may be carried out at 190°C to 270°C, 210°C to 260°C, or 230°C to 255°C, with a condensation rate of 0.9 torr or less, 0.7 torr or less, 0.2 torr to 1.0 torr, 0.3 torr to 0.9 torr, or 0.4 torr to 0.6 torr, for 1.5 to 5 hours, 2 to 5 hours, or 2.5 to 4.5 hours.
[0171] Furthermore, a titanium-based catalyst or a germanium-based catalyst may be added to the prepolymer before the polymerization condensation reaction. Also, before the polymerization condensation reaction, one or more additives selected from the group consisting of silica, potassium, or magnesium; amine-based stabilizers such as trimethylphosphate, triphenylphosphate, trimethylphosphine, phosphoric acid, phosphorous acid, or tetraethylenepentaamine; and polymerization catalysts such as antimonitor trioxide, antimony trioxide, or tetrabutyl titanate may be added to the prepolymer.
[0172] The number-average molecular weight of the polymer may be 40,000 g / mol or more. For example, the number-average molecular weight of the polymer may be 43,000 g / mol or more, 45,000 g / mol or more, or 50,000 g / mol to 70,000 g / mol. By satisfying the above range for the number-average molecular weight of the polymer, the physical properties, impact resistance, durability, and moldability can be further improved.
[0173] Subsequently, pellets can be produced from the polymer. Specifically, the polymer can be cooled to 15°C or below, 10°C or below, or 6°C or below, and then the cooled polymer can be cut to produce pellets.
[0174] The aforementioned cutting step can be performed using any pellet cutting machine used in this industry without limitation, and the pellets may have various shapes. The method of cutting the pellets may include the underwater cutting method or the strand cutting method.
[0175] [Biodegradable polyester sheet] On the other hand, in one embodiment of the present invention, a biodegradable polyester sheet can be obtained using the biodegradable polyester resin.
[0176] For example, the biodegradable polyester sheet may be manufactured using the biodegradable polyester resin or polyester resin pellets.
[0177] Specifically, the prepared polyester resin can be placed, for example, in a stainless steel (SUS) frame, held at approximately 150°C to 300°C under a pressure of 5 MPa to 20 MPa for 1 to 30 minutes using a hot press, then removed and immediately cooled in 18°C to 25°C water for approximately 10 seconds to 5 minutes to produce a biodegradable polyester sheet.
[0178] [Biodegradable polyester film] In one embodiment, the present invention provides a biodegradable polyester film comprising a biodegradable polyester resin, wherein the biodegradable polyester resin comprises a first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit comprising a second diol residue and an aliphatic dicarboxylic acid residue, the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by formula 1 is 2.2 or higher.
[0179] The thickness of the biodegradable polyester film may be between 5 μm and 200 μm. For example, the thickness of the biodegradable polyester film may be between 5 μm and 180 μm, 5 μm and 160 μm, 10 μm and 150 μm, 15 μm and 130 μm, 20 μm and 100 μm, 25 μm and 80 μm, or 25 μm and 60 μm.
[0180] The physical properties of the biodegradable polyester film, such as impact absorption energy, hardness, and thermal shrinkage rate, can satisfy the range mentioned for the biodegradable polyester resin.
[0181] On the other hand, the biodegradable polyester film can be manufactured using the biodegradable polyester resin or polyester resin pellets.
[0182] Specifically, the method for producing the biodegradable polyester film includes: a first step of mixing a diol component and an aromatic dicarboxylic acid and pre-treating it to obtain a slurry; a second step of performing an esterification reaction at least once using a mixture containing the slurry and an aliphatic dicarboxylic acid, or a mixture containing a reaction product obtained by esterifying the slurry and an aliphatic dicarboxylic acid, to obtain a prepolymer; a third step of performing a condensation polymerization reaction of the prepolymer to obtain a polymer; a fourth step of producing pellets from the polymer; and a fifth step of drying and melt-extruding the pellets.
[0183] Stages 1 through 4 are as described above.
[0184] In the fifth step, the drying may be carried out at 60°C to 100°C for 2 to 12 hours. Specifically, the drying may be carried out at 65°C to 95°C, 70°C to 90°C, or 75°C to 85°C for 3 to 12 hours, or 4 to 10 hours. By satisfying the above range of conditions for the pellet drying process, the quality of the biodegradable polyester film or molded article produced can be further improved.
[0185] In the fifth step, the melt extrusion may be carried out at a temperature of 270°C or lower. For example, the melt extrusion may be carried out at a temperature of 265°C or lower, 260°C or lower, 255°C or lower, 150°C to 270°C, 150°C to 255°C, or 150°C to 240°C. The melt extrusion may be carried out by an inflation film (blown film) process.
[0186] According to an embodiment of the present invention, inorganic substances and other additives do not need to be added when manufacturing the biodegradable polyester film. Specifically, by satisfying the range of specific structure and specific physical properties of the biodegradable polyester resin, the biodegradable polyester film can achieve excellent physical properties, biodegradability, and water degradability without adding inorganic substances and other additives during the manufacturing of the biodegradable polyester film.
[0187] [Biodegradable polyester molded products] In one embodiment of the present invention, a biodegradable polyester molded article can be manufactured using the biodegradable polyester resin.
[0188] In other words, the polyester molded article contains a biodegradable polyester resin, the biodegradable polyester resin comprising a first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, and a second repeating unit comprising a second diol residue and an aliphatic dicarboxylic acid residue, wherein the ratio (X / Y) of the number of the first repeating units (X) to the number of the second repeating units (Y) is 0.8 to 3.0, and the impact strength index (ISI) expressed by formula 1 is 2.2 or higher.
[0189] Specifically, the molded article may be manufactured by molding the biodegradable polyester resin by methods known in the industry, such as extrusion or injection molding. The molded article may be, but is not limited to, an injection-molded article, an extruded article, a thin-film molded article, a blow-molded or inflation-molded article, a 3D filament, or an interior building material.
[0190] For example, the molded product may be in the form of a film or sheet that can be used as agricultural mulching film, disposable gloves, disposable film, disposable envelope, food packaging material, garbage bag, etc. It may also be in the form of a fiber that can be used as a woven fabric, knitted fabric, nonwoven fabric, rope, etc., or it may be in the form of a container that can be used as a food packaging container such as a lunch box. Furthermore, the molded product may also be a molded product of various shapes such as disposable straws, spoons, plates, forks, etc.
[0191] In particular, since the molded articles can be formed from the biodegradable polyester resin, which can improve physical properties such as impact absorption energy and hardness, as well as impact resistance and durability, they can exhibit excellent properties when applied to packaging materials for products stored and transported at low temperatures, automotive interior materials requiring durability, garbage bags, mulching films, and disposable products.
[0192] (Examples) The present invention will be described in more detail below with reference to the following examples. However, the following examples are for illustrative purposes only, and the scope of the present invention is not limited to these examples.
[0193] (Example 1) [Preparation of biodegradable polyester resin] <Stage 1: Pre-treatment to obtain slurry> As shown in Table 1, 1,4-butanediol (1,4-BDO) and terephthalic acid (TPA) were mixed in a molar ratio (1,4-BDO:TPA) of 1:1 and introduced into a slurry tank (the bottom of the slurry tank was anchor-type, with a height of 30 mm to the agitator and equipped with three rotating blades) without a catalyst. At this time, the D50 of terephthalic acid (TPA) was 50 μm, and the standard deviation (SD) of terephthalic acid (TPA) to D50 was 40.
[0194] Next, the mixture was pretreated by stirring at 70°C at 150 rpm for 30 minutes to obtain a slurry without phase separation.
[0195] <Stage 2: Obtaining the prepolymer> The slurry obtained in the first step was introduced into the reactor via a supply line, and 200 ppm of tetrabutyl titanate (Dupont®, Tyzor® TnBT), a titanium-based catalyst, was added to it. The primary esterification reaction was then carried out at 230°C and atmospheric pressure for approximately 2 hours until 95% of the by-product water was discharged.
[0196] To the reaction product, 40 mol% of 1,4-butanediol (1,4-BDO) based on the total moles of the diol component, 40 mol% of adipic acid (AA) based on the total moles of the dicarboxylic acid component, and tetrabutyl titanate (Tyzor TnBT, Dupont), a titanium-based catalyst, were added at a concentration of 150 ppm based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. A secondary esterification reaction was then carried out at 200°C and atmospheric pressure for approximately 2 hours until 95% of the byproduct water was removed, thereby preparing a prepolymer with a number-average molecular weight of 5000 g / mol.
[0197] <Stage 3: Condensation polymerization reaction> To the prepolymer obtained in the second step, 150 ppm of tetrabutyl titanate (Dupont, Tyzor TnBT), a titanium-based catalyst, and 600 ppm of triethyl phosphate stabilizer were added based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid, and the mixture was stabilized for approximately 10 minutes. Subsequently, the reaction mixture was heated to 250°C, and a condensation polymerization reaction was carried out at 0.5 torr for 4 hours to prepare a polymer having a number-average molecular weight of 50,000 g / mol. After cooling to 5°C, this polymer was cut with a pellet cutter to obtain biodegradable polyester resin pellets.
[0198] [Manufacturing of biodegradable polyester sheets] After preparing two Teflon sheets, a stainless steel (SUS) frame (area 12cm x 12cm) was placed on one of the Teflon sheets. Approximately 7g of the manufactured polyester resin pellets were placed in the stainless steel (SUS) frame (area 12cm x 12cm), then covered with the other Teflon sheet, and placed in the center of a hot press (With Lab, WL 1600SA) with a surface area of approximately 25cm x 25cm. This was held at approximately 210°C under a pressure of approximately 10 MPa for approximately 3 minutes, then removed, and immediately cooled in water at approximately 20°C for approximately 30 seconds to produce a biodegradable polyester sheet with an area of approximately 10cm x 10cm and a thickness of approximately 300 μm.
[0199] [Manufacturing of biodegradable polyester film] The biodegradable polyester resin pellets were dried at 80°C for 5 hours, and then melt-extruded at 160°C using an inflation film extruder (Blown Film Extrusion Line, YOOJIN ENGINEERING) to produce a biodegradable polyester film with a thickness of 50 μm.
[0200] (Example 2) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced in the same manner as in Example 1, except that different TPAs with different D50 and standard deviations (SD) were used, the amounts of 1,4-butanediol (1,4-BDO), terephthalic acid (TPA), and adipic acid (AA) were changed, and 700 ppm of sonicated cellulose nanocrystals (CNC) (particle size 190 nm) for 1 minute was added when adding 1,4-butanediol (1,4-BDO) and adipic acid (AA).
[0201] (Example 3) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced using the same method as in Example 1, except that dimethyl terephthalate (DMT) was used instead of terephthalic acid (TPA) and the content of each raw material was changed.
[0202] (Example 4) <Stage 1: Pre-treatment to obtain slurry> Based on the total number of moles of diol components, 70 mol% of 1,4-butanediol (1,4-BDO) and 70 mol% of terephthalic acid (TPA) were mixed based on the total number of moles of dicarboxylic acid components. The mixture was then introduced into a slurry tank (with an anchor-type bottom, a height of 15 mm to the agitator, and equipped with two rotating blades) in a catalyst-free state. The D50 of the terephthalic acid (TPA) was 50 μm, and the standard deviation (SD) of the terephthalic acid (TPA) relative to D50 was 20.
[0203] Subsequently, the mixture was pretreated by stirring at 80°C at 180 rpm for 15 minutes to obtain a slurry without phase separation.
[0204] <Stage 2: Obtaining the prepolymer> The slurry obtained in the first step was fed into the reactor via a supply line, with 30 mol% of 1,4-butanediol (1,4-BDO) based on the total number of moles of diol components, and 30 mol% of adipic acid (AA) based on the total number of moles of dicarboxylic acid components. Then, 300 ppm of tetrabutyl titanate (Dupont, Tyzor TnBT), a titanium-based catalyst, was added based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. The esterification reaction was then carried out at 230°C and atmospheric pressure for approximately 3 hours until 95% of the byproduct water was discharged, to prepare a prepolymer with a number-average molecular weight of approximately 4000 g / mol.
[0205] <Stage 3: Condensation polymerization reaction> To the prepolymer obtained in the second step, tetrabutyl titanate (Dupont, Tyzor TnBT), a titanium-based catalyst, was added at a concentration of 150 ppm based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid. After raising the temperature to 245°C, a condensation polymerization reaction was carried out at 0.5 torr for 4 hours to prepare a polymer with a number-average molecular weight of approximately 50,000 g / mol. After cooling to 5°C, this was cut with a pellet cutter to obtain biodegradable polyester resin pellets.
[0206] [Manufacturing of biodegradable polyester sheets and films] Biodegradable polyester sheets and films were manufactured using the same method as in Example 1.
[0207] (Example 5) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced in the same manner as in Example 2, except that in the first and second steps the amounts of 1,4-butanediol (1,4-BDO), terephthalic acid (TPA), and adipic acid (AA), and the content of sonicated cellulose nanocrystals (CNC) (particle size 190 nm) for 1 minute were changed, and in the third step 200 ppm of tetrabutyl titanate (Dupont, Tyzor TnBT), a titanium-based catalyst, was added based on the total weight of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid, and the temperature was raised to 240°C.
[0208] (Example 6) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced using the same method as in Example 1, except that the content of each raw material was changed.
[0209] (Comparative Example 1) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced in the same manner as in Example 4, except that the first step (pretreatment step) of Example 4 was omitted, the amounts of terephthalic acid (TPA) and adipic acid (AA) were changed, and TPA with different D50 and standard deviation (SD) was used.
[0210] (Comparative Example 2) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and biodegradable polyester film were produced using the same method as in Comparative Example 1, except that the amounts of terephthalic acid (TPA) and adipic acid (AA) were changed.
[0211] (Comparative Example 3) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and polyester film were produced using the same method as in Comparative Example 1, except that the amounts of terephthalic acid (TPA) and adipic acid (AA) were changed and TPA with different D50 and standard deviation (SD) was used.
[0212] (Comparative Example 4) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and polyester film were produced using the same method as in Comparative Example 1, except that the amounts of terephthalic acid (TPA) and adipic acid (AA) were changed and TPA with different D50 and standard deviation (SD) was used.
[0213] (Comparative Example 5) As shown in Table 1 below, biodegradable polyester resin, biodegradable polyester sheet, and polyester film were produced in the same manner as in Example 1, except that the first step (pretreatment step) of Example 1 was omitted, the amounts of terephthalic acid (TPA) and adipic acid (AA) were changed, and TPA with different D50 and standard deviation (SD) was used.
[0214] [Table 1]
[0215] (Example of evaluation) [Evaluation Example 1: Average particle size (D50) and standard deviation] <Average particle size (D50) and standard deviation of aromatic dicarboxylic acids> From the particle size distribution (PSD), the average particle size (D50) and standard deviation (SD) of aromatic dicarboxylic acids (TPA or DMT) were determined using a Microtrac S3500 particle size analyzer (Microtrac Inc.) under the following conditions.
[0216] -Usage environment- - Temperature: 10℃~35℃, Humidity: 90%RH, non-condensing maximum — The average particle size distribution (D50) and standard deviation (SD) for each section were measured. The aforementioned standard deviation refers to the square root of the variance and can be calculated using software.
[0217] <Particle size of nanocellulose> For nanocellulose, particle size and particle size deviation were measured using the principle of dynamic light scattering (DLS) at a temperature of 25°C and a measurement angle of 175° using Zetasizer® Nano ZS (Marven). In this process, the peak value derived from the polydispersity index (PdI) with a confidence interval of 0.5 was measured as the particle size.
[0218] [Evaluation Example 2: Impact Absorption Energy (IA)] The impact absorption energy was evaluated using Toyo Seiki's Film Impact Test.
[0219] Using the biodegradable polyester resins produced in the examples and comparative examples, a biodegradable polyester sheet test piece with an area of 10 cm × 10 cm was struck with a triangular pyramidal head with a diameter of 16 mm and a height of 14 mm. The impact absorption energy was calculated by dividing the amount of impact absorption energy by the thickness to obtain the impact absorption energy (kJ / m). The formula for calculating the impact absorption energy (kJ / m) is as follows.
[0220] [Formula 7] Impact absorption energy (IA) (kJ / m) = Amount of impact absorption energy (kJ) / Thickness (m)
[0221] [Evaluation Example 3: Hardness (Shore D)] Based on ISO 868 and ASTM D2240, biodegradable polyester resins manufactured in the examples and comparative examples were used to prepare 3 mm thick biodegradable polyester sheet test specimens, and their hardness was measured using a Shore D tester from DeFelsko.
[0222] [Evaluation Example 4: Impact Strength Index (ISI)] Using the aforementioned shock absorption energy and hardness results, the impact strength index (ISI) expressed by the following formula 1 was calculated.
[0223] [Formula 1] JPEG0007936832000010.jpg13128 In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a 10cm x 10cm test specimen is struck with a triangular pyramidal head with a diameter of 16mm and a height of 14mm. H3T is the hardness measured on a 3mm thick specimen using a Shore D hardness tester, based on ISO 868 and ASTM D2240.
[0224] [Evaluation Example 5: Thermal shrinkage rate (TS) 50 )] The biodegradable polyester films produced in the examples and comparative examples were cut into 150 mm long and 2 cm wide pieces regardless of direction to create test specimens. The initial length at room temperature and the length of the biodegradable polyester film test specimens after being kept in a 50°C convection (hot air) oven for 5 minutes were measured, and the thermal shrinkage rate was evaluated by calculating it using the following formula 2.
[0225] [Formula 2] In the above formula 2, L 25 This is the initial length of a biodegradable polyester film test specimen manufactured from biodegradable polyester resin at 25°C. L 50 This is the length of a biodegradable polyester film test specimen made from biodegradable polyester resin after being exposed to a 50°C hot air blower for 5 minutes.
[0226] [Evaluation Example 6: Thermal Distortion Index (TD)50 )] The aforementioned thermal shrinkage rate (TS 50 Using the results of the impact strength index (ISI), the thermal deformation index (TD) is expressed by the following formula 3. 50 ) was calculated.
[0227] [Formula 3] In the above formula 3, JPEG0007936832000012.jpg12128, 50 And ISI is as defined above.
[0228] [Evaluation Example 7: Storage modulus, loss modulus, loss tangent (tanδ)] The storage modulus and loss modulus of biodegradable polyester sheet specimens prepared in the examples and comparative examples were measured using a RDS (Rheometrics Dynamic Spectrometer, TA Instrument, Discovery HR 30), a dynamic viscoelasticity testing machine.
[0229] Furthermore, using the values of the storage modulus and loss modulus, the loss tangent (tanδ) expressed by the following equation 4 was calculated.
[0230] JPEG0007936832000013.jpg2061 In the above formula 4, G' is the storage modulus of the biodegradable polyester sheet produced from the biodegradable polyester resin at 240°C and a frequency of 5 rad / s in dynamic viscoelasticity measurements. G'' is the loss modulus of elasticity of the biodegradable polyester sheet produced from the biodegradable polyester resin at 240°C and a frequency of 5 rad / s in dynamic viscoelasticity measurements.
[0231] [Evaluation Example 8: Water Decomposition Rate Decrease] The biodegradable polyester sheets produced in the examples and comparative examples were immersed in 80°C water (100% RH), and then subjected to an accelerated water decomposition test.
[0232] Specifically, 5g of the polyester sheets from the examples and comparative examples were placed in 500mL of deionized water (DI Water), then the container was sealed to prevent evaporation, and an accelerated water splitting test was conducted in a convection oven at 80°C. The humidity environment for the biodegradable polyester sheets was the same as that of 100% RH, as they were immersed in water.
[0233] Using gel permeation chromatography (GPC), the number-average molecular weight of the biodegradable polyester sheet after 3 months was compared to the initial number-average molecular weight, as shown in Equation 5 below.
[0234] [Formula 5] In the above formula 5, Mn A and Mn B This refers to the number-average molecular weight of the biodegradable polyester sheet, which was manufactured from the biodegradable polyester resin, after being immersed in water and accelerated by water splitting at 80°C in a convection oven, and then measured using gel permeation chromatography (GPC). Mn A This is the initial number-average molecular weight of the biodegradable polyester sheet, Mn B This is the number-average molecular weight of the biodegradable polyester sheet three months after the acceleration of water splitting was implemented.
[0235] [Evaluation Example 9: Biodegradability] Based on KS M3100-1, the degree of biodegradation was measured by measuring the amount of carbon dioxide generated. Specifically, an inoculum container containing only compost produced at a composting plant was prepared, and a test container was prepared by adding a test piece equivalent to 5% by weight of the dry weight of the compost to the compost. Subsequently, the containers were incubated for 180 days under conditions of a temperature of 58±2°C, a moisture content of 50%, and an oxygen concentration of 6% or higher. The carbon dioxide generated in each container was collected and the amount of carbon dioxide generated in each container was measured by titration with an aqueous phenolphthalein solution. The degree of biodegradation was calculated using the measured amount of carbon dioxide generated according to the following formula 6.
[0236] [Formula 6] JPEG0007936832000015.jpg11146
[0237] [Evaluation Example 10: Inflation moldability and injection moldability] <Inflation moldability> At a temperature of 160°C using an inflation molding machine, air was blown from below to observe bubble formation, and the presence or absence of peeling on the film surface during winding was observed, and the inflation moldability was evaluated as follows. ○: The shape of the bubble is good without being biased to one side or torn, or the surfaces do not adhere to each other during winding △: The shape of the bubble is slightly regular, or slightly extends and biases to one side but the bubble does not burst, or the surfaces slightly adhere to each other during winding but are easily peeled off ×: The bubble does not form a proper shape, or extends and biases to one side, or the bubble bursts, or the surfaces adhere to each other and cannot be peeled off during winding
[0238] <Injection moldability> Meanwhile, using the biodegradable polyester resins prepared in Examples and Comparative Examples, a biodegradable polyester sheet with a thickness of 400 μm was obtained using an injection molding machine at 190°C for about 15 minutes. Regarding the biodegradable polyester sheet, the injection moldability was evaluated as follows. ○: When placed on the mold of the injection molding machine and punched at a temperature of 190°C, it does not adhere to the mold surface and can be easily detached, or no shrinkage occurs and there is no deformation △: When placed on the mold of the injection molding machine and punched at a temperature of 190°C, it adheres to the mold surface but can be detached, or slight shrinkage occurs and slight deformation occurs ×: When placed on the mold of the injection molding machine and punched at a temperature of 190°C, it adheres to the mold surface and is difficult to detach, or shrinkage occurs and deformation occurs
[0239] [Table 2]
[0240] As can be seen from Table 2 above, when the biodegradable polyester resins of the examples that satisfy all of the ranges of the ratio (X / Y) of the number of the first repeating units and the second repeating units and the impact strength index (ISI) within specific ranges are used, the impact resistance and durability are excellent as a whole.
[0241] Specifically, when the biodegradable polyester resins of Examples 1 to 6 are used, the impact strength index (ISI) is 2.26 or more, which is improved compared with Comparative Examples 1 to 5 in which the impact strength index (ISI) is 1.23 to 2.12.
[0242] In addition, when the biodegradable polyester resins of Examples 1 to 6 are used, the impact absorption energy is 6 KJ / m or more, the hardness is 32 or more, the thermal shrinkage rate is 30% or less, and the thermal deformation index (TD 50 ) is also 0.15 or less, so that the impact resistance and durability are remarkably improved while biodegradation occurs, and both inflation moldability and injection moldability are excellent.
[0243] On the other hand, when the biodegradable polyester resins of Comparative Examples 1 to 5 are used, the impact absorption energy and hardness are significantly lower than those when the biodegradable polyester resins of Examples 1 to 6 are used, and the thermal shrinkage rate is also increased compared with the biodegradable polyester films of Examples 1 to 6.
[0244] It was also confirmed that the physical properties of the biodegradable polyester resin, sheet or film vary depending on the ratio of the number of the first repeating unit containing the first diol residue and the aromatic dicarboxylic acid residue to the second repeating unit containing the second diol residue and the aliphatic dicarboxylic acid residue.
[0245] Specifically, when using the biodegradable polyester resins of Comparative Examples 2, 3, and 5, which do not satisfy the ratio of the number of first repeating units containing a first diol residue and an aromatic dicarboxylic acid residue to the number of second repeating units containing a second diol residue and an aliphatic dicarboxylic acid residue, the impact strength index (ISI) is significantly reduced compared to when using the biodegradable polyester resins of Examples 1-6 and Comparative Examples 1 and 4, and the thermal distortion index (TD) is significantly reduced. 50 The ) increased significantly, and both inflation moldability and injection moldability were very poor.
[0246] Furthermore, it was confirmed that adding nanocellulose alters the physical properties of biodegradable polyester resin, sheets, or films.
[0247] Specifically, in Examples 2 and 5, in which nanocellulose was added, the impact absorption energy, hardness, and impact strength index (ISI) increased significantly, while the thermal shrinkage rate and thermal deformation index (TD) increased. 50 The following also decreased, indicating further improvements in durability and impact resistance. In particular, comparing Examples 2 and 4, where the ratio of the number of first repeating units to the number of second repeating units is the same, it can be seen that the impact absorption energy, hardness, and thermal shrinkage rate change depending on the presence or absence of the nanocellulose. That is, when the nanocellulose was added, the physical properties increased overall. This is also true for Examples 3 and 5, where the ratio of the number of first repeating units to the number of second repeating units is the same.
[0248] On the other hand, it was confirmed that the physical properties of the biodegradable polyester resin or film change depending on the process conditions for the biodegradable polyester resin.
[0249] Specifically, when using the biodegradable polyester resins of Examples 1-3 and 5, which were prepared by primary and secondary esterification reactions, the impact strength index (ISI) and thermal distortion index (TD) were within an appropriate range compared to when using the biodegradable polyester resin of Example 4, which was prepared by primary esterification reaction only. 50 We confirmed that this method is more advantageous in achieving the desired result, and that the physical properties have also improved.
[0250] Furthermore, even after primary and secondary esterification reactions, the biodegradable polyester resin of Comparative Example 5, which did not undergo slurry pretreatment, exhibited reduced impact resistance and durability compared to the biodegradable polyester resin of the example that underwent slurry pretreatment. Its inflation moldability and injection moldability were also inferior, making it difficult to expand its applications to a wide range of uses.
[0251] On the other hand, it was confirmed that the impact strength index (ISI) of the biodegradable polyester resin increased as its impact strength index (ISI) increased. For example, in the case of the biodegradable polyester resins of Examples 1 to 5, the impact strength index (ISI) was 2.7 or higher, and it was confirmed that both the impact strength index (ISI) and hardness were improved compared to Example 6, which had an impact strength index (ISI) of 2.25, and Comparative Examples 1 to 5.
[0252] In particular, in Examples 1 to 5, where the number of first repeating units was the same as or greater than the number of second repeating units, it was confirmed that the effects targeted by the present invention were improved overall.
Claims
1. A first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, A biodegradable polyester resin comprising a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, The first diol residue and the second diol residue are each residues of 1,4-butanediol or a derivative thereof. The aromatic dicarboxylic acid residue is a residue of terephthalic acid, dimethyl terephthalate, or a derivative thereof. The aliphatic dicarboxylic acid residue is an adipic acid or a derivative thereof. The ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is between 0.8 and 3.
0. Biodegradable polyester resin having an impact strength index (ISI) of 2.2 or higher, as shown in Formula 1 below: [Formula 1] In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a test specimen with an area of 10 cm x 10 cm is struck with a triangular pyramidal head with a diameter of 16 mm and a height of 14 mm. H3T is the hardness measured on a 3 mm thick specimen using a Shore D hardness tester, based on ISO 868 and ASTM D2240.
2. The biodegradable polyester resin according to claim 1, wherein the number of first repeating units is the same as the number of second repeating units, or the number of first repeating units is greater.
3. The aforementioned biodegradable polyester resin has a thermal shrinkage coefficient (TS) expressed by the following formula 2. 50 The biodegradable polyester resin according to claim 1, wherein the content of ) is 30% or less: [Formula 2] In the above formula 2, L 25 This is the initial length of a biodegradable polyester film test specimen manufactured from biodegradable polyester resin at 25°C. L 50 This is the length of a biodegradable polyester film test piece made from biodegradable polyester resin after being exposed to a 50°C hot air blower for 5 minutes.
4. The aforementioned biodegradable polyester resin has a thermal distortion index (TD) expressed by the following formula 3. 50 The biodegradable polyester resin according to claim 3, wherein the ratio is 0.15 or less: [Formula 3] In the above formula 3, TS 50 And ISI is as defined above.
5. The aforementioned IA is 6 kJ / m or more. The biodegradable polyester resin according to claim 1, wherein the H3T is 32 Shore D or higher.
6. The biodegradable polyester sheet produced from the aforementioned biodegradable polyester resin has a storage modulus measured at 240°C and a frequency of 5 rad / s in dynamic viscoelasticity measurement of 200000 dyne / cm 2 to 400000 dyne / cm 2 , and a loss modulus of 220000 dyne / cm 2 to 450000 dyne / cm 2 , the biodegradable polyester resin according to claim 1.
7. The biodegradable polyester resin described above has a water decomposition rate reduction rate of 50% or more, as shown in the following formula 5, according to claim 1: [Formula 5] In the above formula 5, Mn A and Mn B This refers to the number-average molecular weight of the biodegradable polyester sheet, which was manufactured from the biodegradable polyester resin, after being immersed in water and accelerated in a convection oven at 80°C, and then measured using gel permeation chromatography (GPC). Mn A This is the initial number-average molecular weight of the biodegradable polyester sheet, Mn B This is the number-average molecular weight of the biodegradable polyester sheet three months after the acceleration of water splitting was implemented.
8. The diol component further comprises residues of 1,2-ethanediol, 1,3-propanediol, or a derivative thereof, The biodegradable polyester resin according to claim 1, further comprising succinic acid, sebacic acid, or a derivative thereof as an aliphatic dicarboxylic acid residue.
9. The first step involves mixing a diol component with an aromatic dicarboxylic acid and pre-treating it to obtain a slurry, A second step involves performing an esterification reaction at least once using a mixture containing the slurry and an aliphatic dicarboxylic acid, or a mixture containing the reaction product obtained by esterifying the slurry and an aliphatic dicarboxylic acid, to obtain a prepolymer. The third step involves a condensation polymerization reaction of the prepolymer, A first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, A biodegradable polyester resin comprising a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, The first diol residue and the second diol residue are each residues of 1,4-butanediol or a derivative thereof. The aromatic dicarboxylic acid residue is a residue of terephthalic acid, dimethyl terephthalate, or a derivative thereof. The aliphatic dicarboxylic acid residue is an adipic acid or a derivative thereof. The ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is between 0.8 and 3.
0. A method for producing a biodegradable polyester resin having an impact strength index (ISI) of 2.2 or higher, as shown in Formula 1 below: [Formula 1] In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a test specimen with an area of 10 cm x 10 cm is struck with a triangular pyramidal head with a diameter of 16 mm and a height of 14 mm. H3T is the hardness measured using a Shore D hardness tester on a 3 mm thick specimen, based on ISO 868 and ASTM D2240.
10. Contains biodegradable polyester resin, The aforementioned biodegradable polyester resin is A first repeating unit comprising a first diol residue and an aromatic dicarboxylic acid residue, A biodegradable polyester resin comprising a second repeating unit containing a second diol residue and an aliphatic dicarboxylic acid residue, The first diol residue and the second diol residue are each residues of 1,4-butanediol or a derivative thereof. The aromatic dicarboxylic acid residue is a residue of terephthalic acid, dimethyl terephthalate, or a derivative thereof. The aliphatic dicarboxylic acid residue is an adipic acid or a derivative thereof. The ratio (X / Y) of the number of first repeating units (X) to the number of second repeating units (Y) is between 0.8 and 3.
0. Biodegradable polyester molded products having an impact strength index (ISI) of 2.2 or higher, as shown in Formula 1 below: [Formula 1] In the above formula 1, IA and H3T are values obtained by excluding units measured on biodegradable polyester sheet test specimens manufactured from the biodegradable polyester resin. IA is the impact absorption energy (kJ / m) when a test specimen with an area of 10 cm x 10 cm is struck with a triangular pyramidal head with a diameter of 16 mm and a height of 14 mm. H3T is the hardness measured using a Shore D hardness tester on a 3 mm thick specimen, based on ISO 868 and ASTM D2240.
Citation Information
Patent Citations
Production of polyester
JP2000001533A
KR2012